Epigenetic regulation of phenotype - Whitelaw, Emma (Henry Stewart Talks, 2007)
When does epigenetic reprogramming during the transfer of DNA between parents and their offspring occur, in the gametes or in early development?, inheritance of epigenetic marks can occur, meaning that information other than DNA sequence can be passed on from parent to offspring, the influence of parental environmental history on an individual's epigenetic state, does epigenetic inheritance have an adaptive value?, could epigenetic state be used to give a better estimate of disease risk?
Archived at 2018/10/28